Views of Rome, then and now - Levit, Herschel; Piranesi, Giovanni Battista, 1720-1778 (New York : Dover Publications, 1976)
Piranesi's masterful representations of architecture are now reprinted in large format alongside corresponding contemporary photographs. Monuments of ancient, early Christian, Renaissance and Baroque Rome (Colosseum, Forum, fountains, etc.) with auxiliary notes on both the etchings and photographs. 82 plates.
Bibliography: p. viii.
Keywords: Piranesi, Giovanni Battista, -- 1720-1778.; Rome (Italy) -- In art; Rome (Italy) -- Pictorial works